Obyek Ilmu Kebidanan dalam Perspektif Ilmu menurut Prof. Dr. Ahmad Tafsir sebagai Arah Pengembangan Ilmu Kebidanan - Ngadiyono Ngadiyono; Elisa Ulfiana; Bahiyatun Bahiyatun (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2014)
One of the requirement of science is having an object (Ahmad Tafsir 1992:15). Science object are generaly problems about material object and forma object. Material Object is the main aim of the investigation in the form a material of thinking or research. Form Object explains the important meaning, positions, and function of object in science. Science according to the form object ussually has differences and kinds,form and character.Literature study is done as source of the data, with efort finding the explanation, argumentation, and also comparation with other general science objects which are used in the science treasure, especially the explanation of science according to DR.Ahmad Tafsir.People making a definition of midwifery in the perspective science, with delivering aims, characters, and methods of the science itself. While,the object is concluded:no category if the science object is not explicit to the science theory, the other category has explanation about the science object of midwifery but, must be more focused.Thus, the importance of the midwifery science object as the development of science so it has to be found as the basic step to develope and find or decide, which is appropriate to the science theory nowadays. And also can be done personaly or by science group whice are initiatived by profession by uniting ideas of the scientist on a forum.